2012
DOI: 10.1080/09585192.2011.654347
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of further training – evidence for Germany

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 30 publications
2
41
0
3
Order By: Relevance
“…This result was consistent with the findings presented elsewhere (Castaño-Muñoz et al 2016) that showed how in Spain specifically, the unemployment rate 2 for individuals with higher education was 14 % in the first quarter of 2015 3 and double (29 %) among comparable MOOC learners. On the other hand, lack of employer support for professional development was usually associated to low level responsibility or routine jobs (Grund and Martin 2010) where there was no need for high level skills. Therefore, workers who are not supported by their employers were possibly motivated to take MOOCs in order to substitute the lack of training from their employers and to increase their chances of moving to a better job, which possibly would match better with the typically high educational level of MOOC learners.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…This result was consistent with the findings presented elsewhere (Castaño-Muñoz et al 2016) that showed how in Spain specifically, the unemployment rate 2 for individuals with higher education was 14 % in the first quarter of 2015 3 and double (29 %) among comparable MOOC learners. On the other hand, lack of employer support for professional development was usually associated to low level responsibility or routine jobs (Grund and Martin 2010) where there was no need for high level skills. Therefore, workers who are not supported by their employers were possibly motivated to take MOOCs in order to substitute the lack of training from their employers and to increase their chances of moving to a better job, which possibly would match better with the typically high educational level of MOOC learners.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Warto zaznaczyć, że TKL stanowi dominującą perspektywą teoretyczną, służącą analizie rozwoju pracowników na gruncie ekonomii [Nisar, 2004;Leuven, 2005], jest również wykorzystywana w badaniach dotyczących szkoleń umiejscowionych w naukach o zarządzaniu [np. : Mainga, Hirschsohn, Shakantu, 2009;Grund, Martin, 2012] 2 .…”
Section: Szkolenia W śWietle Różnych Perspektyw Teoretycznychunclassified
“…Furthermore, small and medium sized enterprises show a below-average training level (Blundell et al 1999;Bellmann & Leber, 2008), while big enterprises are likely to show the highest participation in training (Green, 1991;Shields, 1998;Grund & Martin, 2010 (Bellmann & Leber, 2008). Furthermore, training is more likely to occur in the first half to one year of job tenure, which is consequence of increased investments in the skills required for the new job (Green, 1991).…”
Section: The Determinants Of Training: a General Overviewmentioning
confidence: 99%